GAMBARAN TINGKAT PENGETAHUAN TENTANG POLA DIET DIABETES MELLITUS DIWILAYAH KERJA PUSKESMAS GAMBIRSARI SURAKARTA - Ramadhana, Yusuf; Istiningtyas, Anita; Solikhah, Maula Mar’atus (Universitas Kusuma Husada Surakarta, 2020)
Diabetes Mellitus is a metabolic disorder characterized by an increase in glucose levels in the blood. Efforts can be done to maintain glucose levels within normal limits, namely by dietary patterns. The success of managing diabetes mellitus is very dependent on the patient's efforts in changing his behavior from knowledge, attitudes, and practices. The purpose of this study was to determine the characteristics of respondents and describe the level of knowledge of diabetes mellitus dietary patterns in the working area of the Gambirsari Public Health Center in Surakarta. The type of this research is quantitative with a cross-sectional design. The population was typed 2 DM patients with 30 samples taken using a purposive sampling technique with inclusion and exclusion selection criteria. The research instrument used a questionnaire that has been tested for validity and reliability. The results showed the characteristics of the respondents were in the early age of 46-55 years was 23 (76.7%), female sex was 21 (70.0%), and respondents who had a high school education of 21 (70.0%). The description of the level of respondents' knowledge regarding diabetes dietary patterns was sufficient (86.7%). In the description of knowledge about diabetes mellitus dietary patterns in the working area of Gambirsari Public Health Center can be concluded insufficient criteria.